Impacto de la Inteligencia Artificial en la Arquitectura Contemporánea: Evaluación de la relación entre la inteligencia artificial y el diseño arquitectónico. - López Naranjo, David Gilberto (2026)
This research examines how Artificial Intelligence (AI) is reshaping contemporary architectural design and how it affects creativity, efficiency, and professional accountability. Given the rapid diffusion of digital tools, the study discusses which design activities may be automated without weakening contextual judgment, project decision-making, or design authorship. Conducted within the academic setting of UNACH in Riobamba, Ecuador, the methodology combines a focused literature review with surveys and semi-structured interviews involving architecture students and practitioners. To identify measurable shifts, three development modes are compared: a conventional workflow without AI, a workflow where AI supports specific tasks, and a highly automated AI-driven approach. The comparison considers execution time, technical accuracy, breadth of design options, and the degree of critical control over outcomes. Results indicate that AI can accelerate routine tasks and provide analytical assistance, improving productivity and enabling faster iteration. At the same time, it may foster overreliance, contribute to standardized outputs, and reduce traceability when human validation is insufficient. In the Ecuadorian context, these risks are especially relevant for academic training, where evaluation of authorship and decision rationale is essential. Accordingly, the study proposes guidelines for responsible adoption in education and practice, including explicit verification steps, transparent documentation of AI use, and ethical criteria aligned with contextual relevance.